Growth and yield of an eucalyptus subtropical plantation in a Northeastern Mexico degraded land soil - Foroughbakhch Pournavab, Rahim; Carrillo Parra, Artemio; Hernández Piñero, Jorge Luis; Guzmán Lucio, Marco Antonio (2017)
Abstract Over the past three decades, woody species potentially useful for reforestation, fuelwood, coal and timber production have been over-exploited along the Gulf of Mexico, which has led to a gradual decline in the plant population and the progressive degradation of the environment. The present research evaluated the establishment, growth, and production of fuelwood from a plantation of five eucalyptus species planted in randomly arranged plots on a cleared clayey loam alkali soil in a semi-arid region of northeastern Mexico for a 20 year period. Eucalyptus camaldulensis, E. tereticornis and E. microtheca showed the highest average height growth rate (1.07 m year-1, 0.93 m year-1 and 0.85 m year-1, respectively). E. camaldulensis showed the highest volume values at 20 years (58.55 m3 ha-1), followed by E. tereticornis (54.15 m3 ha-1) and E. microtheca (51.91 m3 ha-1). E. sideroxylun and E. crebra yielded the lowest tree volumes (35.12 m3 ha-1 and 30.45 m3 ha-1, respectively). The results have shown that the adaptability of eucalyptus species to the climate of the subtropical regions allows their use in combination with the native vegetation to colonize degraded areas offering services in timber and non-timber products to the local population. In addition, the production of exotic trees with large trunk diameter with few side branches may increase the volume of the wood exploited and the income to the owner of the land and, thus, reduce the pressure on the native species. Keywords: exotic plants, fuelwood production, plant growth, plant survival, semiarid zones, reforestation. Resumen En las últimas tres décadas, las especies leñosas potencialmente útiles para la reforestación, producción de leña, carbón y madera han sido sobreexplotadas en la costa del Golfo de México, lo cual ha dado lugar a una paulatina disminución de la población vegetal y la degradación progresiva del ambiente. En la presente investigación se evaluó el establecimiento, la adaptabilidad, el desarrollo y la producción de leña y carbón de un cultivo de cinco especies de eucalipto por un período de 20 años en parcelas dispuestas al azar en un terreno desmontado con suelo profundo, franco-arcilloso y ligeramente alcalino de la región semiárida del noreste de México. Eucalyptus camaldulensis, E. tereticornis y E. microtheca mostraron la mayor tasa de crecimiento en altura promedio (1.07 m año-1, 0.93 m año-1 y 0.85 m año-1, respectivamente). E. camaldulensis mostró los valores de volumen más altos a los 20 años (58.55 m3 ha−1), seguido de E. tereticornis (54.15m3 ha−1) y E. microtheca (51.91 m3 ha-1). E. sideroxylun y E. crebra arrojaron los volúmenes arbóreos más bajos (35.12 m3 ha−1 y 30.45m3 ha−1, respectivamente). Los resultados obtenidos muestran que la adaptabilidad de las especies de eucalipto al clima de las regiones subtropicales permite su uso en combinación con la vegetación nativa en áreas degradadas ofreciendo servicios en productos maderables y no maderables a la población local. Además, la producción de árboles exóticos de gran diámetro y con pocas ramas laterales puede aumentar el volumen de la madera explotada, los ingresos del propietario de los terrenos y disminuir así la presión sobre las especies nativas. Palabras clave: plantas exóticas, producción de madera, crecimiento, sobrevivencia, zonas semiáridas, reforestación.